ÇOKULUSLU ŞİRKETLERİN FİNANSAL YÖNETİMİNDE TRANSFER FİYATLANDIRMASI VE BİR UYGULAMA - (:unkn) unknown (My University, 2019)
Son yıllarda küreselleşme sonucu çokuluslu şirketlerin yaptıkları işlemler ve fiyatlandırmalar maliye otoritelerinin daha çok dikkatini çekmektedir. Transfer fiyatlandırmasının tanımı, avantajları, vergi mevzuatındaki yeri OECD mevzuatı bağlamında çokuluslu şirketlerin avantajları hakkında değerli hesap uzmanları tarafından eserler yazılmıştır. Bu çalışmada bu bilgiler birleştirilmiş ve bir uygulama ile transfer fiyatlandırmasına tipik bir örnek verilmiştir.

In recent years, with the transactions made by multinational companies had been examined by Tax Authorities of the government and as a result, many books and articles had been written by the Ministry of Finance Bureaucrats. This study integrates all these academic studies and a typical real-life case is given in order to prove the importance of the transfer pricing process. As the globalisation process continues, the transactions of the multinational corporations will become more important for tax authorities. Tax Authorities and Internal Revenue Services had written important research papers on transfer pricing as they are realised by multinational corporations. The purpose of this article is to integrate these studies and give an illustrative example of the transfer pricing process.
TRANSFER PRICING IN FINANCIAL MANAGEMENT OF MULTINATIONAL CORPORATIONS AND AN APPLICATION